HOMA, BMI, and Serum Leptin Levels Variations during Antiviral Treatment Suggest Virus-Related Insulin Resistance in Noncirrhotic, Nonobese, and Nondiabetic Chronic Hepatitis C Genotype 1 Patients - Alessandro Grasso; Federica Malfatti; Gabriella Andraghetti; Simona Marenco; Chiara Mazzucchelli; Sara Labanca; Renzo Cordera; Roberto Testa; Antonino Picciotto (Gastroenterology Research and Practice)
Objective. To investigate the relationship between insulin resistance and viral load decay in nondiabetic and noncirrhotic genotype 1 chronic HCV patients during peginterferon and ribavirin treatment and the possible influence of BMI and leptin as metabolic confounders. Methods. 75 consecutive noncirrhotic, nonobese, and nondiabetic patients with genotype 1 chronic hepatitis C treated with peginterferon alpha 2a plus ribavirin were evaluated. HOMA-IR, serum leptin, and BMI were measured in all patients at baseline and at weeks 12 and 48, whereas viral load was measured at the same time points and then 24 weeks after the end of treatment. Results. HOMA-IR was significantly associated with both BMI and leptin at baseline. During peginterferon plus ribavirin treatment, there was a significant reduction of HOMA-IR at weeks 12 and 48 from baseline (P=0.033 and 0.048, resp.) in patients who achieved an early viral load decay (EVR), a trend not observed in patients who not achieved EVR. No variations during treatment were observed regarding BMI and leptin irrespective of EVR. Conclusion. The early reduction of HOMA-IR but not of BMI and leptin during antiviral treatment in noncirrhotic, chronic hepatitis C genotype 1 patients who achieved EVR suggests a viral genesis of insulin resistance in patients with nonmetabolic phenotype.